Adipose tissue quantity, distribution and pathology and its relationship with type-2 diabetes, insulin resistance and other clustering disease risk in South Asians: a cross-sectional study - Saxena, Aditya; Saran, Sanjay; Choudhary, Praveen; Sharma, Balram; Gupta, Shalu; Mandia, Rajendra; Banshiwal, Ramesh C.; Lamoria, Ravinder Kumar; Dhakad, Anurag; Raj, Utkarsh; Tiwari, Pradeep; Mathur, Sandeep Kumar (Frontiers in Endocrinology, 2025)
BackgroundSouth Asians exhibit distinct metabolic characteristics that may predispose them to insulin resistance (IR), type 2 diabetes (T2D), and metabolic syndrome (MetS). Adipose tissue dysfunction, including abnormal fat distribution and inflammatory processes, has been implicated in metabolic deterioration. However, the specific contributions of adipocyte hypertrophy, ectopic fat accumulation, and immune-related changes remain unclear. Understanding these mechanisms is essential for refining metabolic health interventions.MethodA total of 322 individuals (110 diabetics, 212 non-diabetics) underwent comprehensive clinical, biochemical, and radiological assessments. Body fat distribution, visceral fat, and ectopic liver fat were quantified using dual-energy X-ray absorptiometry (DEXA) and magnetic resonance imaging (MRI). Adipose biopsies were performed to examine adipocyte size and macrophage infiltration across subcutaneous (SAT), visceral (VAT), and femoral fat depots. Metabolic parameters, including MetS score and homeostatic model assessment for insulin resistance (HOMA-IR), were correlated with adipose characteristics.Resultscompared to non-diabetics, diabetics demonstrated significantly higher body mass index (BMI), waist-to-hip ratio, total fat mass, and ectopic liver fat (P < 0.05). While visceral and lower limb fat masses were similar after BMI adjustment, ectopic liver fat remained markedly elevated in diabetics (P = 0.002). Adipocyte hypertrophy was detected in visceral and femoral fat (P = 0.01), with an increased inflammatory macrophage-ratio (M1/M2) observed in subcutaneous fat (P = 0.006). Strong correlations were identified between MetS score, HOMA-IR, BMI, visceral adipocyte size, ectopic liver fat, and macrophage ratio (P < 0.001). However, regional adipose mass lost its correlation with IR and MetS after adjusting for adipocyte size. Inflammatory markers and adipose dysfunction appeared to be central to metabolic deterioration.ConclusionThese insights suggest that interventions aimed at reducing adipocyte hypertrophy, ectopic fat accumulation, and adipose inflammation may offer more targeted strategies for improving metabolic health in South Asians.